Systematic Review and Meta-Analysis on the Effectiveness of Tranexamic Acid in Controlling Bleeding During Transurethral Benign Prostatic Hyperplasia Surgery - Taofiq Olayinka Mohammed; Prashant M. Mulawkar; Pankaj Nandkishore Maheshwari; Abhishek Gajendra Singh; Vineet Gauhar; Gyanendra Sharma (Société Internationale d’Urologie Journal)
Background: Benign prostatic hyperplasia (BPH) is a frequent condition in ageing men. Surgery is recommended for severe BPH symptoms and BPH-related complications. TURP is the reference standard for BPH surgery, but carries a risk of bleeding, which can lead to significant perioperative morbidity and mortality. To reduce bleeding during TURP, antifibrinolytic agents like tranexamic acid (TXA) have been studied. We aim to review the current evidence regarding TXA use during transurethral BPH surgery. Objective: This review aims to assess the efficacy and safety of tranexamic acid in reducing bleeding during transurethral benign prostatic hyperplasia surgery. Methods: Major clinical research databases such as PubMed, Cochrane Central Register of Controlled Trials, EBSCO, Scopus, Google Scholar, and Web of Science were searched from 2012 to 2022 for randomised controlled trials (RCTs) comparing the use of TXA to placebo in transurethral BPH surgery using the PICOS format. We included RCTs without language restrictions that assessed intraoperative blood loss, transfusion rates, haemoglobin levels, length of hospital stay, postoperative thromboembolic events, and 30-day perioperative mortality as outcomes. The quality assessment of the included studies was performed using the Cochrane risk-of-bias tool, RoB 2, for randomised studies. Results: A total of six RCTs, which included 456 patients, were eventually included in the meta-analysis. The results showed that tranexamic acid is beneficial in reducing blood loss and minimising changes in haemoglobin levels during transurethral resection of the prostate. However, it does not lessen the need for blood transfusions or shorten the hospital stay. Conclusions: Tranexamic acid is useful in decreasing blood loss and reducing changes in haemoglobin in patients undergoing transurethral resection of the prostate. Its utility during BPH surgery in low-resource settings where the latest haemostatic enucleation techniques, such as holmium and GreenLight laser enucleation, may not be readily available needs further evaluation.